Asuhan Keperawatan Ketidakefektifan Pola Nafas Dengan Asma Bronkial di IGD RSUD Patut Patuh Patju Gerung Lombok Barat - Yulianti Fitriani (Jurnal Rumpun Ilmu Kesehatan, 2023)
Bronchial asthma is a chronic respiratory disease that often impairs the quality of life of sufferers. Bronchial asthma is characterized by inflammation of the respiratory tract that causes narrowing of the bronchi, swelling, and increased production of mucus. The purpose of this study was to provide nursing care for the ineffectiveness of nasfas patterns with bronchial asthma in the Emergency Room of Patut Patuh Patju Hospital, Gerung, West Lombok. Researchers used a case study method with stages of the nursing process including assessment, formulation of nursing diagnoses, planning, implementation, evaluation and documentation. Nursing care for the ineffectiveness of breathing patterns in AI with bronchial asthma in the emergency room of the Patut Patuh Patju Hospital, Gerung, West Lombok, which was carried out for 3x24 hours, obtained the results that the patient was no longer short of breath, the rhythm of breathing was regular and there was no additional breath sound.